Modern concepts about the chronology of the Muravin (Mikulin, Eemian) interglacial in the west of the Eastern European Plain - Yelovicheva, Yadviga K.; Pisarchuk, Natalia M. (Journal of the Belarusian State University. Geography and Geology, 2024)
The article presents updated materials on the palynological study of stratotype and reference sections of the Muravin (Mikulin, Eemian) interglacial and absolute dating of sediments and also offered a modern look at the geochronology of the fifth marine isotope stage. Research conducted on the basis of the parliamentary conference provides evidence of palynological data on sections of the west of Eastern European Plain with geochronological scales of the northern hemisphere. Consistent sedimentation record in paleoarchives, a new methodological approach in the sequential serial study of organogenic rocks in borehole cores and natural outcrops (every 1–5 cm), complex palynological and absolute dating methods based on conjunctive analysis over the past 10 years, lake-marsh evidence has been studied in great detail measurements and obtain more approximate materials that clarify the chronostratigraphic point of the last and warmest Muravin (Mikulin, Eemian) interglacial.